Influencias y evolución del pensamiento político de fray Servando Teresa de Mier - Diego-Fernández Sotelo, Rafael (El Colegio de México, A.C., 1998)
Fate had Fray Servando Teresa de Mier come to be side by side with the American delegates that participated in the Courts of Cádiz, after he passed from Portugal to Spain in 1808 to join the resistance against the Napoleonic invasion. This moment was determinant, and represented the trigger thar made him fight with all his strenght against the Spanish government, to defend the liberty and absolute independence of America. This is the cornerstone that allows us to undersand all Fray Servando's life and thought from that moment to his death.Considering that Mier became one of the most meaningful figures in the American independence movemnt, it is important to undersant clearly his motivations, his main ideas, his political beliefs, and his ideological models. True enough, from his conversion in 1808 to his full maturity, as representative of an independent Mexico, his thought evolved deeply, to the point that in many occasions he abandoned, without a doubt, ideas and convictions he had defended strongly at other times.All in all, the clarity of his goals and political stands' saved him from shipwrecking in a turbulent and agitated sea of wideranging political theories, originated in many points of Europe and America and struggling to impose themselves. After the deceiving experience in the Courts of Cádiz, Fray Servando left wishing to realize two dreams for all America: that of liberty and that of absolute -not relative, as some authors were beginning to suggest at that time- independence.